Implementasi Program Pemberdayaan Sosial Kegiatan Rehabilitasi Sosial Rumah Tidak Layak Huni (RTLH) bagi Masyarakat Miskin di Kabupaten Pandeglang - Ismowati, Mary; Subhan, Ahmad (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2018)
The government in 2012 held a Non-Livable House (RTLH) program for the poor which aims to improve the condition of the house as a whole and partly so as to create a decent home.             In 2017, there were only 227 recipients of the RTLH Program in Pandeglang district (23.03%). This shows the inequality of program assistance. In fact, some regions did not get the program at all. Some are not right on target for the RTLH program. Another problem is due to the limited budget for the RTLH Program, while the number of people who need a lot.             Qualitative research was used in this study. There are 24 informants obtained by Purposive techniques. The focus of this research is how the Implementation of Non-Eligible Houses (RTLH) Program Policies in the villages of the District of Labuan in Pandeglang Regency using the theory of Charles O ’Jones which consists of three dimensions, namely: organization, interpretation and application.             Based on the results of the research and processing of the data, it can be concluded that the Implementation of the Policy for the Non-Eligible Houses (RTLH) Social Rehabilitation Guidelines for the poor in the Pandeglang District Social Service has not gone well. The successful implementation of the Non-Eligible Houses (RTLH) social rehabilitation policy for the poor in Pandeglang District Social Service has not been fully successful.